Impact of Clot Location on Outcomes after Mechanical Thrombectomy for Anterior Circulation Acute Ischemic Stroke: A Meta-Analysis. (16th November 2020) - Sujijantarat, Nanthiya; Koo, Andrew B; Elsamadicy, Aladine A; Hebert, Ryan M; Cord, Branden J; Navaratnam, Dhasakumar; Sansing, Lauren; Malhotra, Ajay; Matouk, Charles C
Abstract: INTRODUCTION: Prior studies have suggested a predictive value of computed tomography (CT)-based clot characteristics including location on clinical outcome after mechanical thrombectomy (MT) for anterior circulation acute ischemic stroke (AIS). This meta-analysis aims to provide an up-to-date evaluation of these characteristics on clinical outcome and recanalization success. METHODS: We searched Cochrane Library, Embase, and MEDLINE databases for English articles reporting the effects of CT-based clot characteristics on outcomes after AIS between 2000–2019. The primary outcome was good functional status, as defined by modified Rankin Scale (mRS) ≤ 2 at 90 days. Secondary outcomes were recanalization success, symptomatic intracerebral hemorrhage (sICH), and mortality. The results were pooled with random and fixed effect models. RESULTS: 2, 933 records were identified through database searches. Of these, 33 studies were included in the qualitative synthesis. Clot burden score, location, distance to ICA terminus, length, volume, and attenuation were independent variables of interest. Of these variables, only clot location contained sufficient quantitative data for meta-analysis. Seven articles enrolling 2, 306 patients with data on clot location and dichotomized mRS were identified. These included patients from a total of 8 randomized trials and 12 institutional cohorts. MCA occlusion was associated with a good functional outcome (pooled odds ratio [OR]: 1.38, 95% confidence interval [CI]: 1.12-1.70 for M1; pooled OR: 1.74, 95% CI: 1.16-2.62 for M2 and beyond) compared to ICA occlusion. Of the studies with the primary outcome of interest, 4 reported on recanalization outcomes and 3 reported on sICH and mortality. ICA occlusion was associated with increased mortality (pooled OR: 2.23, 95% CI: 1.64-3.04) compared to MCA occlusion. There were no differences in recanalization success and sICH by clot location. CONCLUSION: In patients undergoing MT for AIS, ICA compared to MCA clot location as determined by pre-intervention CT angiography is associated with lower odds of good functional outcome and higher odds of mortality. Due to a lack of quantitative data in the published literature, the impact of other clot characteristics on stroke outcomes is better investigated by systematic review.